Literature Review: Model Edukasi Menyusui Untuk Suami - Agus Rahmat Hidayat; Sarah Handayani (Jurnal Kesehatan, 2022)
Breastfeeding can prevent annual deaths in children, including having a positive impact on the country's economy and even at the family level. Men are often forced to be involved in breastfeeding and caregiving, but the approach of the Maternal and Child Health (MCH) program is too girly, which often makes men feel alienated. Breastfeeding education for men is not impossible. This paper tries to describe several models that have been shown to have a positive impact on breastfeeding success using the literature review method. The results show that some face-to-face models for 2-3 hours can be done with several sessions for 2-3 weeks. Other models without face-to-face can also be done, for example by providing flyers, booklets, and disseminating information through mass media including education through Facebook and WhatsApp groups and smartphone applications. The government and health services should start seeing men as subjects in the MCH program and start developing breastfeeding education activities for fathers, even if breastfeeding education activities are combined with mothers, they should use a gender-free approach.